On the mechanisms of taurine in alleviating electrocardiographic, hemodynamic, and biochemical parameters following aluminum phosphide cardiotoxicity. (August 2021) - Samadi, Mahedeh; Baeeri, Maryam; Haghi-Aminjan, Hamed; Rahimifard, Mahban; Gholami, Mahdi; Hassani, Shokoufeh; Sattari, Mohammadreza; Azarmi, Yadollah; Bameri, Behnaz; Armandeh, Maryam; Hooshangi Shayesteh, Mohammad Reza; Eghbal, Mohammad A.; et al.
Abstract: Background: Aluminum phosphide (AlP) causes severe cardiotoxicity. Taurine has been chosen for the present study because of its positive known effects on cardiac injuries. Method: To evaluate AlP-induced cardiotoxicity, the animals were divided into seven groups, including the control group, the taurine group (500 mg/kg), AlP with LD50 dose, AlP + taurine 20, 50, 100, and 200 mg/kg group. To assess cardiac hemodynamic parameters, Wistar rats received taurine intraperitoneally 60 min after AlP gavage. Cardiac hemodynamic parameters were evaluated for 180 min. To study biochemical parameters, 24 h after AlP treatment, the animals were sacrificed, and heart tissues were collected. Result: ECG, BP, and HR abnormalities of AlP poisoning were improved by taurine treatment. AlP induced biochemical alterations including complexes I and IV activities, the ADP/ATP ratio, mitochondrial membrane potential, cytochrome C release, and oxidative stress biomarkers ameliorated by taurine. Moreover, taurine improved apoptosis, as well as lessened CK-MB and troponin I levels. Also, there were no significant changes between taurine 500 mg/kg and the control group in tests. Conclusion: The present findings showed that taurine could be a possible candidate for AlP cardiotoxicity treatment via the effect on mitochondrial electron transfer chain and maintaining intracellular ATP balance. Highlights: AlP-induced cardiotoxicity is a significant cause of death in the first 24 h. AlP-induced cardiotoxicity mitigated by taurine. Taurine mitigated cardiac hemodynamic parameters and cardiac biomarkers. Taurine improved mitochondrial function and oxidative stress in cardiotoxicity.